Oxidative stress in polycystic ovary syndrome: a case- control study - Syeda Samira Azim; Zeba Haque; Sadaf Khan; Jahan Ara Hasan; Sidra Zaheer; Sajida Parveen (Journal of the Pakistan Medical Association, 2024)
Objective: To compare the serum levels of biochemical and oxidative stress markers i.e., malondialdehyde (MDA) and paraoxonase-1(PON1) in polycystic ovary syndrome (PCOS) patients and healthy female individuals of reproductive age group (18-40 years). Methods: This case-control study was conducted in Dow University of Health Sciences (DUHS), Karachi from June 2019 to October 2020. Seventy Subjects including 35 PCOS patients that have primary subfertility problem (cases) and 35 healthy and fertile females (controls) were recruited. Serum samples were collected for analysis of insulin, sex hormone-binding globulin, testosterone, fasting blood glucose and lipid profile. PON 1 and MDA levels were estimated by ELISA. Comparison between the two groups was done using independent t-test. Result: The patients had significantly increased mean body mass index (28.5+4.6 kg/m2 vs 25.7+4.5 kg/m2, p=0.014), systolic (129.6±13.9 mm of Hg vs 113±7.7 mm of Hg, p< 0.001) and diastolic (78.7±8.8 mm of Hg vs 74.6±6.7 mm of Hg, p=0.032) blood pressures compared to controls. The high-density lipoprotein cholesterol levels were significantly lower in PCOS (42.2±8.6mg/dl) than controls (48.8±11.8mg/dl, p=0.009, p=0.009). Serum insulin (14.3±5.8 µIU/mL) vs (10.0±5.2 µIU/mL), p=0.002 and testosterone levels (1.3±0.9 nmol/L) vs (0.82±0.3 nmol/L), p<0.001 were significantly higher whereas sex hormone binding globulin (SHBG) levels (35.2±19.7nmol/L vs 58.8±31.0 nmol/L) were significantly lower in patients than healthy controls (p<0.001). Both oxidative stress markers, paraoxonase 1 (7.7±2.4 vs 6.4±2.6 µg/mL, p=0.04) and malondialdehyde (2.5±1.0 vs 1.9+0.51µg/mL, p=0.034) levels were significantly elevated in PCOS patients than controls. No significant correlation was found between dietary habits and life style between cases and controls. Conclusion: The study reported significantly elevated levels of oxidative stress markers in PCOS patients. Keywords: Blood Glucose, Blood Pressure, Testosterone, Oxidative stress, Malondialdehyde, Lipoproteins, Cholesterol, Lipids, Enzyme.